ANALYSIS AND OPTIMIZATION OF DOOR’S JITTER PROBLEM OF A CERTAIN SUV ON TEST FIELD - ZHANG LiQiang; YU Shuang; HU Shuai; ZHANG Song (Jixie qiangdu)
In order to study the jitter problem of the left rear door of a certain SUV on the washboard road with speed of（12 ～ 15） km/h,a transfer path analysis（TPA） model is established by combining the working load test with the transfer function simulation. Based on the complex stiffness method,the dynamic load of the connecting point between the chassis and the car body is obtained. At the same time,the transfer function of the left rear door of the Trimmed Body（TB） model is obtained by the CAE method. The contribution of each transfer path to the target point is calculated. The reliability of the TPA model is verified by compared the combined value of each transfer path with the experimental value. According to the contribution of each path,it is found that the left connection between the lateral stabilizer rod and the car body is the main transfer path. Then,the dynamic stiffness of the connection of the transfer path is optimized to reduce vibration transmission ratio. The result shows that the peak value of the jitter acceleration is reduced from 8017 to 4236（mm/s~2）.